3D-printed bioactive ceramic scaffolds with MoSe2 nanocrystals as photothermal agents for bone tumor therapy. Issue 47 (26th October 2022) - Zhang, Xin; Li, Yingzhi; Dong, Xiaoming; Wang, Hao; Chen, Bo; Li, Ruiyan; Qin, Yanguo; Ivasishin, Orest
Abstract : 3D-printed bioceramic scaffolds functionalized with MoSe2 could be used for bone tumor therapy and bone repair. Abstract : Large scale bone defects after bone tumor resection are difficult to reconstruct and repair, and there is also the possibility of tumor recurrence. Photothermal therapy (PTT) has the function of inhibiting tumor cells, but the risk of damage to normal cells is the main factor limiting the clinical application of PTT drugs, and most of them have a weak effect on regeneration for bone defects. Therefore, specific biomaterials that simultaneously eliminate bone tumors, have low toxicity, and promote osteogenesis have attracted considerable attention. In this paper, we successfully fabricated bioactive bredigite scaffolds (MS-BRT) functionalized with MoSe2 nanocrystals using a combination of 3D printing and hydrothermal methods. MS-BRT scaffolds not only have low toxicity and good osteogenic ability, but also have the ability to kill bone tumors by photothermal therapy. Using scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), and an infrared thermal camera, MoSe2 nanocrystals were demonstrated to be successfully modified on the surface of BRT scaffolds. The MoSe2 nanocrystals endow the scaffolds with excellent photothermal properties, which can be well controlled by varying the hydrothermal reaction time and laser power density. Furthermore, the MS-BRT scaffolds can effectively kill MG-63 and HeLa cells and promote the adhesion and proliferation of osteoblasts. The performance of osteoblastic activity was assessed by alkaline phosphatase staining and alizarin red S staining, which results suggest that both MS-BRT and BRT have favorable osteogenic properties. This study combines the photothermal properties of semiconducting MoSe2 nanocrystals with the osteogenic activity of bioceramic scaffolds for the first time, providing a broader perspective for the development of novel biomaterials with dual functions of bone tumor treatment and bone regeneration.